Production, characterization and utilization of epoxy spherical membrane filter prepared by an advanced aqueous method - Sea Bee Ing (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
Thereby, the idea to produce an epoxy spherical membrane (ESM) with multiple micro-scale pores for industry wastewater treatment is developed. In this research, an advanced aqueous method is use to produce ESM based on the water in oil in water (W/O/W) double emulsion polymerization technique. This method is simple and environmentally friendly because no solvent is used; no emission of volatile product. It is feasible to scale up. Epoxy and polyamide are in liquid form at room temperature that enables to be emulsified.